Wildfire‐Induced Enhancement in Downstream Flood Discharge in Watersheds of California - Wasitha Dilshan; Yusuke Hiraga; So Kazama (Journal of Flood Risk Management)
ABSTRACT Global climate change is increasingly associated with the prevalence of extreme precipitation and large wildfires. The influence of large wildfires on downstream flood discharge is concerning, particularly from a flood risk management perspective, where understanding the impact at a watershed scale is still fairly limited. This study investigates the impacts of wildfires on downstream flood discharge in 30 Californian watersheds. We employed the Soil and Water Assessment Tool (SWAT) to simulate daily discharge over 20 years, achieving robust model performance R2 values of 0.67–0.86 and Nash–Sutcliffe efficiency (NSE) values of 0.65–0.86. The differences between the observed flood discharge volume and the simulated unburned scenario, including model errors (i.e., flood discharge enhancement), during the post‐fire years were assessed. Substantial post‐fire discharge increases, with an average 17.1% increment in 83.3% of watersheds, were found during the first post‐fire year. Statistically significant positive correlations (p < 0.01) were found between the enhancement in discharge volume and the percentage of burned watershed area. We quantified wildfire impacts by adjusting the curve number (CN) in the SWAT model, with CN values increasing by increments ranging from 16.5% to 30% of their original values, depending on burn severity and land use type. A novel relationship between wildfire area burned and CN increment could be described by the equation %CN increment = 0.39 × wildfire area burned % + β, which highlights the proportional increase in CN due to wildfire area burned. The study also showed that incorporating historical wildfire activity significantly raised the probable maximum flood, with discharge volume increases between 3.74% and 25.9%. These wildfire‐induced increases are on par with California's climate change projections (10%–50%), underscoring the need to factor in wildfire effects in flood risk assessments and water management strategies at this type of location.